Horizontal drying fronts in films of colloidal dispersions: influence of hydrostatic pressure and collective diffusion. Issue 48 (27th November 2017) - Nassar, M.; Gromer, A.; Favier, D.; Thalmann, F.; Hébraud, P.; Holl, Y.
Abstract : The origin and time evolution of heterogeneities in drying colloidal films is still a matter of debate. Abstract : The origin and time evolution of heterogeneities in drying colloidal films is still a matter of debate. In this work, we studied the behaviour of horizontal drying fronts in a 1D configuration. The effects of hydrostatic pressure and collective diffusion of charged particles, neglected so far, were introduced. We made use of the new simulation tool based on cellular automata we recently presented (Langmuir 2015 & 2017). To check the simulation results, measurements of film profiles in the wet state and drying front velocities were performed with silica colloids. It was shown that taking hydrostatic pressure into account much improves agreement between theory and experiment. On the other hand, the simulation showed that collective diffusion slows down the drying fronts, even more when the Debye length is increased. This latter effect remains to be checked experimentally. This work opens the way to further improvements of theory and simulation, notably 2D and 3D simulations.